Intense laser field effects on a Woods–Saxon potential quantum well. (November 2015) - Restrepo, R.L.; Morales, A.L.; Akimov, V.; Tulupenko, V.; Kasapoglu, E.; Ungan, F.; Duque, C.A.
Highlights: The increase of ILF leads to important effects on the optical properties of an W–S type QW. The magnetic and electric fields effects are more relevant for large α 0 values. The magnitude of the AC (RI) peak decreases (increases) with α 0 . Abstract: This paper presents the results of the theoretical study of the effects of non-resonant intense laser field and electric and magnetic fields on the optical properties in an quantum well (QW) make with Woods–Saxon potential profile. The electric field and intense laser field are applied along the growth direction of the Woods–Saxon quantum well and the magnetic field is oriented perpendicularly. To calculate the energy and the wave functions of the electron in the Woods–Saxon quantum well, the effective mass approximation and the method of envelope wave function are used. The confinement in the Woods–Saxon quantum well is changed drastically by the application of intense laser field or either the effect of electric and magnetic fields. The optical properties are calculated using the compact density matrix.